(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
About 1 million new cases of the disease are detected worldwide every year. In particular, oncological pathology of the breast occupies a leading place in the system of women’s oncological diseases, and according to statistics, it is confirmed that their number is increasing in recent years. In the general system of diseases among women, breast canser is from 13,5% to 30%, especially in recent decades. It is noted that the disease is growing in economically developed countries is being done. Therefore, it is very important to prevent mastopathy( breast cancer). Mastopathy, fibrocystic mastopathy (FKM) is one of the most common diseases of the mammary glands. According to the statistics of the World Health Organization (WHO), almost every second woman of childbearing age is familiar with this disease.